Gambut Muslim Community and Their Environmental Conservation; Intertwin among Fiqh, Economy, and Policy Factors - Sukarni, Sukarni (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2024)
Islamic eco-theology doctrines encourage believers to care for the environment and forbids destructive actions that could harm or degrade the environmental condition. However, in recent years, many paddy fields and peatlands in Banjar Regency, which should have been preserved for environmental restoration, have been transformed into residential areas. Therefore, this research aims to explore factors influencing the conversion in the Gambut Subdistrict, Banjar Regency, ranging from a religious perspective or fiqh, the economic situation of local people, and relevant regulation enforcement. The research is a field study with a mixed-method approach. Data collection involved 120 respondents residing in the Gambut Subdistrict. Additionally, interviews were conducted with community leaders, organizational representatives, and local government officials. Using a multiple regression approach, the study found that since 2000, 55 new residential complexes have been constructed in the region. The research findings reveal that although economic factors have a minimal impact on environmental conservation variables, fiqh perspectives, and policy variables do affect significantly. These three factors, namely fiqh perspectives, economic factors, and policies collectively exert a significant influence on environmental conservation. Qualitatively, the primary cause of the conversion of paddy fields and peatlands into residential areas is the lack of environmental fiqh literacy. This deficiency has resulted in low awareness of the importance of preserving paddy fields and peatlands as environmental support areas, leaving them vulnerable to encroachment by capital owners eager to develop residential areas. Furthermore, weak oversight by authorities and policymakers has exacerbated this situation.